2016
DOI: 10.5114/ms.2016.62307
|View full text |Cite
|
Sign up to set email alerts
|

Demographic conditioning of awareness of prophylaxis against Streptococcus agalactiae (GBS) infections among parturients

Abstract: Introduction: Infection with Streptococcus agalactiae (group B Streptococcus -GBS) is a frequent cause of serious complications in the neonatal period. Circa 10-30% of pregnant women are carriers of this streptococcus. Current prophylaxis of GBS infections is an elementary way of defining whether there is a risk of the child's infection. The achieved research result determines further perinatal proceedings. Aim of the research:To determine how such factors as age, residence, education, and current women's pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…A comparison of the findings with those reported in studies conducted by Alshengeti et al and Youden et al confirmed a low level of GBS awareness among women [ 7 , 16 ]. In addition, only 7% of women have been requested to undergo GBS testing by their gynecologists, whereas 81.7% of pregnant women in Poland have been tested [ 17 ]. These vastly different percentages are attributable to the existing protocol in Poland’s Kielce Hospital, requiring midwives to collect a swab for GBS screening if a pregnant woman has no clear tests [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the findings with those reported in studies conducted by Alshengeti et al and Youden et al confirmed a low level of GBS awareness among women [ 7 , 16 ]. In addition, only 7% of women have been requested to undergo GBS testing by their gynecologists, whereas 81.7% of pregnant women in Poland have been tested [ 17 ]. These vastly different percentages are attributable to the existing protocol in Poland’s Kielce Hospital, requiring midwives to collect a swab for GBS screening if a pregnant woman has no clear tests [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that more time spent in the country women are residing in can impact knowledge ,34,35 , however this was only supported by two studies. No consistent relationship between knowledge and age 32,35,38,43,45 ; employment status 32,34,35 ; city vs village living 38,44 ; past exposure to GBS 32,40,44,45 ; or parity 32,35,38,44,45 was found.…”
Section: Awareness Of Gbs Is Generally Low (<40%) and Varies Across C...mentioning
confidence: 93%
“…In included studies, awareness of GBS ranged from 8-37% (n = 6; M = 24.78; SD = 9.77) [32][33][34][35][36][37] . Awareness of GBS screening programmes ranged from 9 -67.1% (n = 3; M = 44.27; SD = 25.30) 32,38,39 . This variable knowledge about GBS was corroborated by the qualitative studies which reported most women did not have an extensive knowledge about GBS [40][41][42] .…”
Section: Awareness Of Gbs Is Generally Low (<40%) and Varies Across C...mentioning
confidence: 99%
See 1 more Smart Citation